KEKUATAN AKTA NOTARIS SEBAGAI SYARAT FORMIL PERJANJIAN BISNIS: KAJIAN NORMATIF TERHADAP IMPLIKASI KETIDAKHADIRAN PENGHADAP SECARA LANGSUNG - Fajrul Mumtaz; Yessyca Utami (HUNILA : Jurnal Ilmu Hukum dan Integrasi Peradilan, 2026)
The failure of parties to appear in person before a notary in the execution of business agreements has generated growing legal uncertainty regarding the validity and enforceability of notarial deeds in Indonesian commercial practice. Despite its critical function as the highest form of written evidence under Indonesian civil law, the requirement of personal appearance  as mandated by Law Number 2 of 2014 on the Amendment to Law Number 30 of 2004 concerning Notary Position (UUJN) is frequently circumvented through power of attorney substitution, remote representation, or digital media, creating substantial legal and economic risks for commercial parties. This study aims to: (1) examine the legal standing of personal appearance as an absolute formal requirement in notarial deeds governing business agreements; (2) analyze the juridical implications for deed validity and evidentiary force when such requirement is unmet; and (3) construct a normative framework addressing the resulting legal vacuum to ensure certainty for parties engaged in commercial transactions. Employing a normative juridical method, this research conducts grammatical, systematic, and teleological interpretation of the UUJN, the Indonesian Civil Code (KUHPerdata), and relevant judicial decisions. The findings establish that non-compliance with the personal appearance requirement fundamentally degrades the deed’s legal status from an authentic instrument to a private document, extinguishing its executorial force and rendering commercial parties legally and economically vulnerable. This research recommends a normative reinterpretation of the UUJN that bridges notarial formality requirements with the protection of commercial contract validity.